(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the need to introduce advanced foreign experience in the educational process of training highly qualified personnel in the field of tourism, problems, effective mechanisms for solving problems, and gives sound recommendations from a scientific point of view.